Analysis of the Impact of Zakat, Infak, and Sadaqah Distribution on Poverty Alleviation Based on the CIBEST Model (Case Study: Jogokariyan Baitul Maal Mosque, Yogyakarta) - Salahuddin El Ayyubi; Henni Eka Saputri (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
The Special Region of Yogyakarta is one of the provinces with a high incidenceof poverty onJava Island. The number of mosques and the increase of zakat funds, infak, and sadaqaheach year is not sufficientto reduce the number of those in poverty. If the mosque is able tomanage the zakat, infak, and sadaqahfunds well, it can be predicted that the mosque would reduce poverty and increase the welfare of the community. This study aims to analyze the impact of zakat, infak, and sadaqah distribution in reducing poverty based on the Center for Islamic Business and Economic Studies (CIBEST) model (case study: Jogokariyan Baitul Maal Mosque, Yogyakarta). The results of the study indicate that there is an increase in welfare and a decrease in material poverty, spiritual poverty, and absolute poverty, as seen from changes in the Islamic CIBEST’s poverty indexes formustahik households. Keywords: CIBEST Model, Jogokariyan Mosque, Poverty, ZIS